Pendidikan Inklusi di Lembaga PAUD: Pengaruhnya Terhadap Sosialisasi dan Pengembangan Karakter Anak Usia Dini di TKIT Ibu Harapan - Lia mulyati; Shalihatus Sa'adah; Suci kurnia fitri; Mufaro'ah Mufaro'ah (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2024)
This research aims to analyze the influence of inclusive education at Early Childhood Education (PAUD) institutions on the socialization abilities and character development of early childhood at TKIT IBU HARAPAN. Inclusive education allows children with special needs to learn together with other children in the same environment, so that social interaction and character formation can develop in an inclusive atmosphere. This research uses a qualitative approach, with data collection techniques in the form of observation, interviews and documentation. Through observations, researchers recorded interactions between children in inclusive classes, especially seeing how children with special needs behaved and were accepted in the group. In-depth interviews were conducted with teachers, teaching staff, and parents to gain perspectives on the influence of inclusive education on children's socialization and character, as well as the challenges and successes they experienced. Documentation includes daily activity records, progress reports, and evaluation of the school's inclusion program to understand the overall changes that have occurred. The research results show that inclusive education has a significant positive impact on early childhood socialization abilities, including increasing the ability to share, cooperate and empathize with peers. Children learn to appreciate differences and develop empathy by helping friends in need. Inclusive education has also been proven to support the development of children's character, especially in the aspects of independence, honesty and self-confidence.